2015
DOI: 10.1177/0954405415575476
|View full text |Cite
|
Sign up to set email alerts
|

A systematic selective disassembly approach for Waste Electrical and Electronic Equipment with case study on liquid crystal display televisions

Abstract: Waste Electrical and Electronic Equipment (WEEE) is one of the major waste streams in terms of quantity and toxicity, and a critical step in WEEE end-of-life (EoL) processing is through disassembly. Compared with full disassembly, which is a sub-optimal solution due to its high operational cost, selective disassembly is more economic and practical as only selected parts with recycling potential are considered. In this paper, a systematic selective disassembly approach for handling WEEE with a maximum disassemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…The sequential disassembly plan as shown in Table 1 is obtained by using the conventional sequential disassembly method [4,5] based on the space interference matrix (Appendix). As shown in Table 1, there is no removable part identified at iteration 7, and parts B, C1-2 and D are interlocked.…”
Section: 'Separable Pairs' Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequential disassembly plan as shown in Table 1 is obtained by using the conventional sequential disassembly method [4,5] based on the space interference matrix (Appendix). As shown in Table 1, there is no removable part identified at iteration 7, and parts B, C1-2 and D are interlocked.…”
Section: 'Separable Pairs' Methodsmentioning
confidence: 99%
“…Jin et al [4,5] demonstrated a method based on the space interference matrix to find removable components to generate feasible disassembly sequences. The key point of this method is to find removable components which have freedom in at least one direction.…”
Section: Contact and Relation Matrices: Fundamental Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disassembly model is always built by graph-based method [47,48], Petri Net method [49] and matrix-based method [50,51], etc. For robotic disassembly, feasible disassembly direction of each part should be provided for industrial robots.…”
Section: Disassembly Model For Eolpmentioning
confidence: 99%
“…Considering the changes of disassembly tool, the changes of disassembly direction, the part volume and the maintainability, Kheder used genetic algorithm to obtain optimal disassembly sequence of a rear axle (Kheder, Trigui, and Aifaoui 2015). To disassemble heavy, hazardous and high-value components as early as possible, brute-force method was proposed to obtain the optimal disassembly sequence based on waste electrical and electronic equipments (Jin et al 2015). To simultaneously optimize the disassembly level, recovery options and disassembly sequence, an improved co-evolutionary algorithm was used to find the optimal disassembly solutions (Meng et al 2016).…”
Section: Related Workmentioning
confidence: 99%